Applied Research in the Pursuit of Justice: Creating Change in the Community and the Academy - Joyner, Laurie M. (Social justice, 2003)
Part of a special issue on applied research and social justice. The importance of redefining the relationship between academic sociology and communities in order to sustain the pursuit of social justice is discussed. It is argued that applied research and service learning are two areas through which connections between academic institutions and communities can be strengthened.